UPAYA GURU DALAM PENINGKATAN SELF CONFIDENCE SISWA MELALUI PEMBELAJARAN ACTIVE LEARNING DI SDN GUNDIK - Rosyidah, Nisa Tri Utami; Laksana, Sigit Dwi; Sumaryanti, Lilis (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to describe teachers' efforts in increasing student confidence through Active Learning learning at SDN Gundik. The background of this research is based on the importance of self-confidence as a supporting factor in the success of the student learning process in elementary school. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that teachers carried out various Active Learning strategies, such as group discussions, student presentations, and educational games to create a fun and participatory learning atmosphere. This strategy has been proven to be able to increase students self-confidence in expressing opinions, asking questions, and actively participating in learning. Supporting factors include the teacher's personal approach, a positive classroom environment, and parental involvement. The inhibiting factors faced include differences in student character and time constraints. In conclusion, Active Learning learning has a positive impact on increasing student self-confidence if applied consistently and adjusted to student needs.